Benefits of Rosuvastatin in Cardiovascular Protection Remain Unclear After HOPE-3 (The Review of Diabetic Studies, 2016)
The use of commercialized statins in the pre- vention of cardiovascular diseases (CVD) has commonly been accepted based on the informative results of the Cholesterol Treatment Trialists (CTT) reports [1] As an additional effort in the prevention of CVD, professional societies have issued practical recommendations for healthcare providers on the effective use of statins in lowering low-density-lipoprotein cholesterol (LDL-C) [2]. Among these statins, atorvastatin and rosuvastatin are regarded as the most effective as they can reduce more than 30% of LDL-C, even at low doses (i.e. atorvastatin 10 mg; rosuvastatin 5 mg) [2]. The results of the recent HOPE-3 study [3], in which 10 mg rosuvastatin was found to reduce the development of CVD by 24% in intermediate-risk persons, may reinforce the role of rosuvastatin in CVD prevention. However, there are some concerns regarding the use of rosuvastatin.